Late diagnosis of latent adult autoimmune diabetes (LADA) in an elderly patient with persistent episodes of hypoglycemia: case report (Research, Society and Development, 2021)
Introduction: The concept of latent autoimmune diabetes in adults, whose acronym in English is LADA, for "latent autoimmune diabetes in adults" was first introduced in 1993 by Tuomi and Zimmet to define adult diabetic patients who did not require insulin to control their hyperglycemia in the early stages of the pathology, but they presented autoantibodies against beta-cell proteins and faster progression to the need for insulin. Objective: to show a case report of an elderly patient with LADA who frequently presents hypoglycemic episodes. Methodology: this is a clinical case study with a qualitative and descriptive perspective, which consists of a research that, in general, takes place with direct data collection, in which the researcher is the indispensable instrument. Results and discussion: hypoglycemia triggers a series of counter-regulatory mechanisms: it suppresses insulin secretion by beta cells, stimulates glucagon release by alpha cells, adrenaline release by the adrenal medulla, in addition to cortisol and growth hormone . In addition, it is also observed the release of noradrenaline from postganglionic sympathetic neurons and acetylcholine from sympathetic and parasympathetic postganglionic neurons, in addition to other neuropeptides. Conclusion: patients with type 1 diabetes mellitus often have episodes of hypoglycemia during insulin therapy, which, in addition to discomfort and embarrassing situations in daily life, prevents the achievement of ideal glycemic control. Furthermore, hypoglycemia induces a deficient counter-regulation mechanism in a later episode, with decreased adrenaline release and alarm symptoms, establishing the hypoglycemia syndrome associated with autonomic failure.